(untitled) (Research, Society and Development, 2021)
Introduction: Over the years, the significant change in all levels of society has forced the human being to have the capacity for physical, mental and social adaptation, and, as a consequence, undergraduates experience daily life, becoming vulnerable to stressors, and can thus trigger imbalances in their mental health. Objective: Admission to university can present a threatening situation, since it is an adaptive phase in which the young adult will have more responsibilities and may become more anxious and depressed. In view of this, the objective of this study is to discuss the stressors that affect many undergraduate students, and, from that, to propose preventive measures. Methodology: This is a study carried out through documentary research through an Integrative Review of Literature, considering as source scientific articles that attest to the proposal of this research. As inclusion criteria, publications in Portuguese and English were selected, with texts in full and freely accessible in the databases, from 2012 to 2018. Exclusion criteria were unavailable texts, duplicated in the databases and met the objective of the present study. Results and Discussion: After reading and re-reading the articles and based on the analyzes of the researchers investigated, it was possible to list positive numerical data that reveal the emotional suffering of the undergraduate students. The main evidences were the use of own mental health questionnaires, which guided and emphasized the resolutions of the articles. Conclusion: Analyzing the evidence we can see the vulnerability and stressors that develops numerous emotional psychic imbalances in university students, and can be applied to strategic measures that prevent diseases and promote the mental health of these students.